Stakeholder evaluations of risk interventions for non-potable recycled water schemes: a case study - Goodwin, D.; Raffin, M.; Jeffrey, Paul; Smith, Heather M. (Elsevier, 2019)
Non-potable recycled water schemes can benefit sustainable urban water management through reducing demand for drinking water and mitigating environmental loadings through the provision of advanced wastewater treatment. However, scheme feasibility can be diminished by high capital and operating costs which can be elevated by perceptions of health risks and subsequently overly cautious risk reduction measures. Conversely, a failure to anticipate the risk management expectations of stakeholders can undermine scheme feasibility through insufficient demand for recycled water. The aim of this study was to explore how stakeholders' perceptions and preferences for risk management and recycled water end-uses might influence scheme design. Using a case study scheme in London, four risk management intervention scenarios and six alternative end uses were evaluated using a stochastic PROMETHEE-based method that incorporated quantitative microbial risk assessment and stakeholder criteria weights together with an attitudinal survey of stakeholders' risk perceptions. Through pair-wise criteria judgements, results showed that stakeholders prioritised health risk reductions which led to the more conservative management intervention of adding water treatment processes being ranked the highest. In contrast, responses to the attitudinal survey indicated that the stakeholders favoured maintaining the case study's existing levels of risk control but with more stakeholder engagement. The findings highlighted potential benefits of understanding risk perceptions associated with different design options and contrasting these with multi-criteria model results. Extrapolating from these findings, future research could explore potential challenges and benefits of providing flexibility in scheme designs to appeal to a wider range of stakeholder needs as well as being more adaptable to future social, environmental or economic challenges. The study concludes that contemporary risk management guidance would benefit from more explicitly outlining constructive ways to engage stakeholders in scheme evaluation.
Keywords: Multi-criteria evaluation; Stakeholder engagement; Risk management; Non-potable recycled water